2013
DOI: 10.1179/2046023613y.0000000037
|View full text |Cite|
|
Sign up to set email alerts
|

Fixative properties of honey in comparison with formalin

Abstract: Fixation is an initial and important step in tissue processing for microscopical examination. The primary aim of fixation is to preserve the tissues in a life-like state, prevent bacterial putrefaction, prevent autolysis, and increase the refractive index of the tissue. The present study used a natural fixative instead of chemicals in order to prevent the deleterious effects of the chemical fixatives. The aim of this study was to determine the effectiveness of honey as a fixative, which is a natural product. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 8 publications
1
21
0
Order By: Relevance
“…who compared 10% formalin and with 10% honey solution. [ 8 ] In contrast, Patil et al . in their studies used honey and jaggery for tissue fixation at 20% and 30% concentration, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…who compared 10% formalin and with 10% honey solution. [ 8 ] In contrast, Patil et al . in their studies used honey and jaggery for tissue fixation at 20% and 30% concentration, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…However, the stained cytoplasm was sufficient enough to make out the integrity of the tissue. The cytoplasm of epithelial cells did not undergo any change whereas; the connective tissue cytoplasm exhibited good staining with H&E, with complete homogenization effect on the collagen fibers [12].…”
Section: Natural Alternatives Used For Fixationmentioning
confidence: 96%
“…For several centuries, honey has been documented to possess anti-bacterial, acidic and dehydrative properties. The antiautolysis and tissue hardening property of the honey, besides its wound healing and anti-bacterial nature was highlighted in one of the studies [12]. These are the properties of a fixative that present honey in terms of a fixative rather than a preservative.…”
Section: Natural Alternatives Used For Fixationmentioning
confidence: 99%
“…[7,8] Many different studies have already been done to compare honey as fixative in histopatholgy in comparison to formalin, which has provided convincing and appreciable results. [9][10][11] In honey fixed smears one could very clearly appreciate all cellular details such as nuclear, cytoplasmic staining, cellular morphology, clarity and uniformity of the staining which are almost equivalent to ethanol fixed smears. Present study in concordance with Singh A, et al [4] showed that cellularity and cell morphology were well preserved in honey which provides adequate cytological material for diagnosis.…”
Section: Discussionmentioning
confidence: 99%